Effect of VR simulations on MPA level & breath control of voice major students - Haris, Thio Felicia Yasinta; Purbojo, Rijanto (Jurnal Inovasi Teknologi Pendidikan, 2024)
A form of art that is created through a performance by one or an ensemble of performers, shown in front of an audience is called the performing arts. Despite having its appeal, performing in front of many people can lead to "performance anxiety". Performance anxiety is especially very concerning for singers and voice students. This can lead to diminished performance quality and impair the control of their vocal technique, with the most affected one being their breath control, which is considered one of the most crucial techniques in singing. A survey conducted on voice students of Pelita Harapan University Conservatory of Music has found this as a phenomenon that's been experienced by students, noticed by the voice lecturers, but yet to be effectively addressed. Previously, the use of VR simulations has been found effective in helping treat and decrease the symptoms and occurrence of social anxiety, which includes performance anxiety. However, a very limited amount of research has been done on the impact of VR on music-related performance anxiety (MPA), and even less specifically on singing performances. Through a mixed-method approach and by adopting the within-subject research design, this study aims to study the effects of VR simulation implementation on nineteen voice major students of Pelita Harapan University Conservatory of Music's MPA level and breath control. Results found that the method was effective in treating the MPA symptoms and did improve the students' breath control but was not conducted long or frequently enough to take a long-term or permanent result.